Introduction to concrete anchor rods - Lundin, Reid (Kansas State University, 2012)
Concrete anchors represent an important transition for both the design and construction of a project. Anchors are produced in two main categories: cast-in-place and post-installed. For designers, anchors are used to attach steel members to supporting concrete members. The anchors are designed using the provisions outlined in Building Code Requirements for Structural Concrete, ACI 318-11, Appendix D. These anchors are used to transmit tension and shear forces by using an individual anchor or a multiple anchor group. For contractors, anchor installation marks the transition between concrete and steel construction. Various types of anchors are produced by manufacturers, requiring contractors to be familiar with many installation methods. Careful planning and coordination is necessary to layout and place anchors into their correct location. Once anchors are installed, they must be protected from damage resulting from moving machinery and material. The purpose of this report is to introduce the basics to design concrete anchors by outlining the provisions in ACI 318-11 Appendix D and demonstrating these provisions with design examples. Anchor types, applications and common construction issues important to the structural engineer are also discussed.
Keywords: Cast-in-place concrete anchor rods; ACI 318; Anchor bolts; Architectural engineering (0462)